The Consumer Financial Protection Bureau's Single-Director Structure: A Viable and Constitutional Regulatory Approach? - William Riherd (Bellarmine Law Society Review, 2020)
Riherd's project examines the constitutionality of the single-director structure of the Consumer Financial Protection Bureau (CFPB). By invoking key precedent cases from a span of 100 years of jurisprudence, such as Humphrey's Executor v. United States, Riher explores the history of cause removal provisions and the President's Article II, Section III powers. Riherd concludes his analysis with a pragmatic and viable recomendation to restructure the Bureau to be a bipartisan commission, and highlights the ongoing need for effective and predicatble economic regulation, especially post-Recession.